(untitled) (Foro de Educacion, 2024)
The wearing of fur of lions, leopards and wolves by Herakles, Paris and Dolon, respectively, allows us, throw the study of the features and power attributed to those beasts, to review the importance and the status granted in the Greek world to each of those legendary archers.